Optical Clearing of Cranial Bone. (29th April 2008) - Genina, Elina A.; Bashkatov, Alexey N.; Tuchin, Valery V.
Abstract : We present experimental results on optical properties of cranial bone controlled by administration of propylene glycol and glycerol. Both transmittance and reflectance spectra of human and porcine cranial bone in vitro were measured. For estimation of absorption and reduced scattering coefficients of the bone, the inverse adding-doubling method was used. The decrease of reflectance of the samples under action of the immersion agents was demonstrated. The experiments have shown that administration of the immersion liquids allows for effective controlling of tissue optical characteristics that makes bone more transparent, thereby increasing the ability of light penetration through the tissue. The presented results can be used in developing of functional imaging techniques, including OCT.